Problem of Evil: Hick's Sublimation of Plantinga : . - Panthanmackel, George (Journal of Dharma, 1998)
The problem of evil has always baffled the thinkers of every age, and it continues to be one of the most puzzling ones. Once David Hume raised the old Epicurean question: "Why is there any misery at all in the world? Not by chance, surely. From some cause then. Is it from the intention of the Deity? But he is perfectly benevolent. Is it contrary to his intention? But he is almighty